Penerapan Sistem Informasi Berbasis Komputer Pada Aplikasi Monitoring Keuangan dan Aset (Terkait Penatausahaan Piutang Tuntutan Ganti Kerugian Negara) - Wijaya, Zaenal Sekty (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2015)
Abstract These day, the development of information and technologies in Indonesia is in steady pace and right now also involving other sectors including private and government sectors. Information and technologies has become a common tool that also has been used by many people to support and sustain their daily needs. With the usefulness of the modern technologie, itâs expected that human can invent a new form of system of information that can be used as a tool for running a business or to achieve the organizationâs goals. The information that has been given by the system of information is really vital for some decision makers. The preciseness of a decision that made by the decision makers does rely on the information which they retrieve. If the information is not reliable, it will affect the decision that has been made. If a company or some government institution make the wrong choice, the company will suffer loss or the aim of the institution will never be achieved. Thatâs why many companies spend a lot of money for their system of information so they can get a reliable source of information. A good information is an information which is accurate, actual, and relevant.